Tira cômica: construindo caminhos para a leitura inferencial - Freire, Thiago Domingos (2019)
In the face of technological advances, a consequence of a contemporary society, a diversified educational approach is configured through reading. In this context, text also harbors other semiotic sources of meaning beyond the traditional acceptance of the verbal sign. In addition, the reader, an essential part of the production of meaning, is able to activate different knowledge acquired throughout his personal and school career when encountering a text. In this perspective, the present study considered the difficulties of inferential reading with the comics from 8th grade elementary students of the Jorge Amado State School in Nossa Senhora do Socorro, Sergipe. The objective was to produce a pedagogical book that promotes the development of inferential abilities, indicated by the National Assessment of School Performance or Brazil Test (“Prova Brasil”), through reading strategies. For this reason, we chose to intervene pedagogically in didactic sequence according to the hypothesis of Dolz et al. (2004), favoring the overcoming of the problem found and reflecting the suggestions of the textbook. This proposal has as theoretical base the studies of Dionísio (2005), Leffa (1999), Solé (1998), Marcuschi (2008), Koch (2011) among others. From the presented content, it is possible to affirm that the work constitutes a pedagogical intervention closer to reality in the classroom, since the material planned is based on the indications of external and internalized evaluations of the institution on reading competence. Thus, this document gains relevance both for personalization in meeting a specific demand and replicable in other contexts, as well as in the promotion of continuing teacher education that reflects on the educational role and the teacher's posture versus available didactic resources.